2010
DOI: 10.1088/1367-2630/12/3/033024
|View full text |Cite
|
Sign up to set email alerts
|

Entropy and information causality in general probabilistic theories

Abstract: We investigate the concept of entropy in probabilistic theories more general than quantum mechanics, with particular reference to the notion of information causality recently proposed by Pawlowski et al. (arXiv:0905.2992). We consider two entropic quantities, which we term measurement and mixing entropy. In the context of classical and quantum theory, these coincide, being given by the Shannon and von Neumann entropies respectively; in general, however, they are very different. In particular, while measuremen… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
187
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(199 citation statements)
references
References 37 publications
(43 reference statements)
1
187
0
Order By: Relevance
“…They also studied the distinguishability measures and entropies in GPT [9,10]. In [11,12], the authors introduced the entropy and discussed some other problems in GPT from the perspective of information causality. The incompatibility of the two postulates, that is, the dynamical evolution postulate and the wave-packet collapse postulate, has always been a fundamental problem in the foundations of quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…They also studied the distinguishability measures and entropies in GPT [9,10]. In [11,12], the authors introduced the entropy and discussed some other problems in GPT from the perspective of information causality. The incompatibility of the two postulates, that is, the dynamical evolution postulate and the wave-packet collapse postulate, has always been a fundamental problem in the foundations of quantum mechanics.…”
Section: Introductionmentioning
confidence: 99%
“…Working from this peculiar perspective, it can be shown that many phenomena usually considered as typically quantal, like quantum no-cloning and no-broadcasting theorems, the trade-off between state disturbance and measurement, and the existence and basic properties of entangled states, are in fact generic features of nonclassical probabilistic theories that verify a basic non-signaling constraint [1]. This is the point of departure of our present considerations.…”
Section: Introductionmentioning
confidence: 79%
“…The answer is given in, for example, [11] and [12]. Several possible applications were envisaged in [13][14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…It is clear from the diagrammatic notation that given scalars s and s we have s • s = s ⊗ s = s ⊗ s = s • s; i.e. the scalars form a commutative monoid 3 .…”
Section: Theories and Diagramsmentioning
confidence: 99%
“…The latter have recently received much attention because one can better understand a theoryquantum theory in particular-by studying it as merely a member of a broader class of theories. Notably, the study of non-locality within this framework has provided important new insights [2,3]. Whereas generalised probabilistic theories discard everything except the convex probabilistic structure, in contrast, GCTs focus on composition.…”
mentioning
confidence: 99%